2007
DOI: 10.1001/archneur.64.12.1798
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Ultrasound as a Diagnostic Adjunct in Common Peroneal Neuropathy

Abstract: High-Resolution Ultrasound as a Diagnostic Adjunct in Common Peroneal Neuropathy E ntrapment neuropathy of the common peroneal nerve is caused mostly by compression at the fibula head region. 1 In cases of severe axon loss, demonstration of conduction block or reduction of conduction velocity would be difficult. Apart from demyelination, mechanical factors and ischemic mechanisms may play a role. 2 Differing degrees of damage to individual nerve fascicles may occur within the common peroneal nerve, 3 rendering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 6 publications
(2 reference statements)
3
18
1
Order By: Relevance
“…To date, many studies have reported that ultrasonographic measurement is a beneficial diagnostic tool for nerve disorders with significant positive correlation with electrodiagnostic study [111516171819]. Ultrasonography visualizes the anatomy of the affected structures and provides morphological information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, many studies have reported that ultrasonographic measurement is a beneficial diagnostic tool for nerve disorders with significant positive correlation with electrodiagnostic study [111516171819]. Ultrasonography visualizes the anatomy of the affected structures and provides morphological information.…”
Section: Discussionmentioning
confidence: 99%
“…In case of CFN at the FH secondary to the intraneural ganglion cyst that needs surgical procedure, ultrasonography leads to more accurate prognosis by detecting the etiology, which might not be identified by electrophysiological study alone [15]. Moreover, if electrodiagnostic study is performed inadequately or insufficiently, ultrasonography could be a supplementary tool for accurate diagnosis by differentiating from lesions that mimic CFN at the FH such as high sciatic nerve lesion [11]. Ultrasonography in addition to electrodiagnostic study reportedly improves specificity to 88% in CFN at the FH [10] and sensitivity up to 98% in ulnar neuropathy at the elbow [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology of nerve swelling and thickening is complex, and may involve endoneural edema, demyelination, axonal degeneration, and fibrosis [16,17]. To this end, future research may further explore this intriguing issue [18].…”
Section: Discussionmentioning
confidence: 99%